1997
DOI: 10.2741/a207
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and cancer

Abstract: Prostaglandins (PGs) are lipids produced enzymatically and nonenzymatically from 20 carbon fatty acids, particularly arachidonic acid. Prostaglandins and related metabolites (collectively referred to as eicosanoids), including the thromboxanes, prostacyclins, hydroperoxy and hydroxy fatty acids, and leukotrienes are produced by most tissues of the body by oxidation of arachidonic acid, although the amount and class of product varies with cell type. The biological action of many of these eicosanoids as key regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 148 publications
2
43
0
1
Order By: Relevance
“…Melanocyte dendrites are important for prevention of cutaneous cancers because of the requirement for dendrites in the transfer of photoprotective pigment-laden melanosomes to keratinocytes. We identified the expression of two of the four EP receptors for PGE 2 on melanocytes in vitro (EP 1 and EP 3 ) and showed that signaling by these receptors could independently stimulate the formation of dendrites in melanocytes [7]. Prior reports have shown that the EP 3 receptor is expressed in the basal epidermal layer, where melanocytes reside [40] and our data shows that human melanocytes express EP 3 in vivo.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Melanocyte dendrites are important for prevention of cutaneous cancers because of the requirement for dendrites in the transfer of photoprotective pigment-laden melanosomes to keratinocytes. We identified the expression of two of the four EP receptors for PGE 2 on melanocytes in vitro (EP 1 and EP 3 ) and showed that signaling by these receptors could independently stimulate the formation of dendrites in melanocytes [7]. Prior reports have shown that the EP 3 receptor is expressed in the basal epidermal layer, where melanocytes reside [40] and our data shows that human melanocytes express EP 3 in vivo.…”
Section: Discussionsupporting
confidence: 55%
“…The effects of prostaglandins and the cross talk between prostaglandin receptors and their signaling intermediates are of intense interest because of the diverse effects of prostaglandins on cell growth, differentiation and carcinogenesis [3,38,[41][42][43]. While the effects of PGE 2 on epidermal keratinocytes are reasonably well understood [1,[43][44][45], there has been much less investigation in the effects of PGE 2 on human melanocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations